Meteorological and astronomical knowledge of Mongolian-speaking nomads in the mirror of the natural landscape lexicon in weather and climate discourse: based on folklore and artistic texts - E. U. Omakaeva (Nomadic Civilization: Historical Research)
The article is devoted to the specifics of verbalization of traditional meteorological and astronomical knowledge in the meteorological lexicon and weather-climatic discourse of Mongolian-speaking nomads. Nomadic linguistic culture can be represented as a system of mental representations represented by the keywords of the text. Meteorological and astronomical phenomena play an important role in a person’s understanding of the surrounding reality. A special place in the worldview of a nomad is occupied by the climatic and weather conditions of the area, which have a significant impact on his daily life, economic activities, everyday life, behavior, etc. The accumulated knowledge about atmospheric phenomena is consolidated in the meteorological lexicon, a special system of lexical units denoting meteorological phenomena. The object of the study is meteolexicon, which characterizes the climate and state of the atmosphere (weather) in a certain area, as well as astronyms (nominations of point celestial objects) and cosmonyms (proper names of outer space zones). The relevance of their study on Mongolian-language material is due to insufficient knowledge of the issue. The formation of meteorological vocabulary depends on the climatic characteristics of the territory, on the specifics of the economy and life of the population. The names of celestial bodies (stars, constellations, etc.) are closely related to material and spiritual culture. This is a most valuable resource for a comprehensive understanding of the historical experience of the Mongols and Kalmyks in the field of traditional environmental management.